An unusual case of acute transverse myelitis caused by HSV-1 infection. (2016) - Figueroa, Danisha; Isache, Carmen; Sands, Michael; Guzman, Nilmarie
Abstract: Transverse myelitis is a neurological disorder of the spinal cord that can have a variety of etiologies. Herpes simplex virus (HSV) infection has been described as one of the causes, most commonly HSV type 2. We report here a case of an 18 year old male who presented with weakness that started in his upper extremities and rapidly evolved to quadriplegia. Magnetic resonance imaging of spine was consistent with transverse myelitis. HSV type 1 PCR testing on cerebrospinal fluid (CSF) was positive. He was started on acyclovir and steroids, but despite therapy, patient did not recover motor function.